2008
DOI: 10.1037/0735-7036.122.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Object permanence tests on gibbons (Hylobatidae).

Abstract: Ten gibbons of various species (Symphalangus syndactylus, Hylobates lar, Nomascus gabriellae, and Nomascus leucogenys) were tested on object permanence tasks. Three identical wooden boxes, presented in a linear line, were used to hide pieces of food. The authors conducted single visible, single invisible, double invisible, and control displacements, in both random and nonrandom order. During invisible displacements, the experimenter hid the object in her hand before putting it into a box. The performance of gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…de Blois & Novak, 1994;de Blois et al, 1998;Deppe et al, 2009;Fedor et al, 2008;Mendes & Huber, 2004;Neiworth et al, 2003]. We also analyzed all the trials in the sequential visible task in the present study, for comparison with past research.…”
Section: Visible Displacementsmentioning
confidence: 98%
See 2 more Smart Citations
“…de Blois & Novak, 1994;de Blois et al, 1998;Deppe et al, 2009;Fedor et al, 2008;Mendes & Huber, 2004;Neiworth et al, 2003]. We also analyzed all the trials in the sequential visible task in the present study, for comparison with past research.…”
Section: Visible Displacementsmentioning
confidence: 98%
“…de Blois & Novak, 1994;Natale, 1989;Neiworth et al, 2003], one gibbon [Fedor et al, 2008], domestic cats and dogs [see Dumas, 1987 andGoulet, 1998 for reviews], a few lemur species [Deppe et al, 2009], and bottlenose dolphins [Jaakkola et al, 2010, but see discussion regarding a training procedure implemented, which might have contributed to success]. Furthermore, research indicates that single visible displacements are easier to solve than double visible displacements [e.g.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Research to date indicates that Piagetian visible displacement tasks with some form of control can be solved by all great ape species (Natale 1989;de Blois et al 1998;Call 2001;Barth and Call 2006), one gibbon (Fedor et al 2008), several monkey species (e.g., Natale 1989;de Blois and Novak 1994;Neiworth et al 2003), a few lemur species (Deppe et al 2009), domestic cats and dogs (see Dumas 1987 andGoulet 1998 for reviews), and bottlenose dolphins (Jaakkola et al 2010). Research also indicates that among nonhuman animals, only the great ape species (orangutans, gorillas, bonobos, and chimpanzees) can solve single invisible controls and adjacent double invisible displacements without the use of associative strategies (de Blois et al 1998;Call 2001;Barth and Call 2006;CollierBaker and Suddendorf 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several gibbon behavioral characteristics could explain their apparent lack of abilities and contradicting results of previous studies. Gibbons have notoriously short attention spans [Fedor et al, 2008] potentially losing interest after only a few trials, impeding learning set formation. Also, gibbons rely heavily on their visual cognitive abilities-it has been found that gibbons are competent in detecting the visual orientation of other species as well as their own and possess some knowledge of how visual gaze direction relates to external stimuli [Horton & Caldwell, 2006].…”
Section: Introductionmentioning
confidence: 99%